2020
DOI: 10.3390/jcm9020568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radial Extracorporeal Shock Wave Therapy on Pain Intensity, Functional Efficiency, and Postural Control Parameters in Patients with Chronic Low Back Pain: A Randomized Clinical Trial

Abstract: Low back pain (LBP) is the leading cause of disability worldwide, placing a significant economic burden on healthcare systems. Radial extracorporeal shock wave therapy (rESWT) is useful in the rehabilitation of orthopedic diseases; however, there is still limited evidence for patients with LBP. The aim of this study was to assess the effect of rESWT on pain level, functional efficiency, and parameters of postural control in patients with LBP. Participants were randomized into group A (n = 20) treated with rESW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…During the last years a number of studies indicated that extracorporeal shock wave therapy (ESWT) may serve as an alternative in treatment of cnsLBP [32][33][34][35][36][37][38][39][40][41][42] (an overview on these studies is provided in Appendix A). However, in none of these studies ESWT was compared with NSAIDs and SMRs, let alone the investigation of potential advantages of the combination of ESWT with NSAIDs and SMRs over respectively ESWT or NSAIDs and SMRs alone.…”
Section: Introductionmentioning
confidence: 99%
“…During the last years a number of studies indicated that extracorporeal shock wave therapy (ESWT) may serve as an alternative in treatment of cnsLBP [32][33][34][35][36][37][38][39][40][41][42] (an overview on these studies is provided in Appendix A). However, in none of these studies ESWT was compared with NSAIDs and SMRs, let alone the investigation of potential advantages of the combination of ESWT with NSAIDs and SMRs over respectively ESWT or NSAIDs and SMRs alone.…”
Section: Introductionmentioning
confidence: 99%
“…Shock waves are de ned as a sequence of single, highly energetic, biphasic acoustic impulses described by rapid propagation of rapidly increased pressure in three-dimensional space applied directly into the tissues without in uencing their global destruction (9). There are two types of ESWT generators, focused (fESWT) and radial (rESWT) and with low or high energy (10,11). The fESWT is generated by electromagnetic, piezoelectric and electrohydraulic sources (10).…”
Section: Introductionmentioning
confidence: 99%
“…The fESWT is generated by electromagnetic, piezoelectric and electrohydraulic sources (10). In this method, the pressure increases quickly to a peak intensity and back downward with a beam that has a concentrated shape with a focal point with the highest energy density (11). In contrast, rESWT is generated by pneumatic methods and the pressure increases slightly, slower, to a lesser intensity and with a dispersed beam shape (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations